A Challenging Case of Postcholecystectomy Pseudoaneurysm at an Uncommon Location - Choudhary, Shayeri Roy; Bhujade, Harish; Gupta, Pankaj; Singh, Harjeet; Kalra, Naveen; Kang, Mandeep (Journal of Clinical Interventional Radiology ISVIR, 2022)
Hepatic artery pseudoaneurysm in postcholecystectomy choleduodenal fistula is an extremely rare but clinically significant complication. A 52-year-old male presented with hematemesis and melena several weeks after open cholecystectomy for complicated gallstone disease. Upper gastrointestinal endoscopy revealed bleeding from the choledochoduodenal fistula site. On computed tomography angiography, a small right hepatic artery pseudoaneurysm close to fistula site was identified. Endovascular embolization failed due to nonopacification of the proximal right hepatic artery. Endoscopic ultrasound-guided embolization was also unsuccessful due to the small size of the aneurysm and inadequate visualization. Following this, percutaneous n-butyl cyanoacrylate glue was successfully injected into the pseudoaneurysm. The patient recovered and was planned for hepaticojejunostomy to restore biliary continuity.
Keywords: biliovascular injury; hepatic artery pseudoaneurysm; endovascular embolization